Manuscript recipe collections and elite domestic medicine in Eighteenth-Century England - Allen, K (2015)
Collecting recipes was an established tradition that continued in elite English households throughout the eighteenth century. This thesis is on medical recipes and advice, and it addresses the evolution of recipe collecting from the seventeenth century and throughout the eighteenth century. It investigates elite domestic medicine within a cultural history of medicine framework and uses social and material history approaches to reveal why elites continued to collect medical recipes, given the commercialisation of medicine. This thesis contends that the meaning of domestic medicine must be understood within a wider context of elite healthcare in order to appreciate how the recipe collecting tradition evolved alongside cultural shifts, and shifts within the medical economy. My re-appraisal of the meaning of domestic medicine gives elite healthcare a clearer role within the narrative of the social history of medicine. Elite healthcare was about choice. Wealthy individuals had economic agency in consumerism, and recipe compilers interacted with new sources of information and products; recipe books are evidence of this consumer engagement. In addition to being household objects, recipe books had cultural significance as heirlooms, and as objects of literacy, authority, and creativity. A crucial reason for the continuation of the recipe collecting tradition was due to its continued engagement with cultural attitudes towards social obligation, knowledge exchange, taste, and sociability as an intellectual pursuit. Positioning the household as an important space of creativity, experiment, and innovation, this thesis reinforces domestic medicine as an important part of the interconnected histories of science and medicine. This thesis moreover contributes to the social history of eighteenth-century England by demonstrating the central role domestic medicine had in elite healthcare, and reveals the elite reception of the commercialisation of medicine from a consumer perspective through an investigation of personal records of intellectual pastimes and patient experiences.